A Highly Sustainable Timber-Cork Modular System for Lightweight Temporary Housing - Francesco Barreca; Natale Arcuri; Giuseppe D. Cardinali; Salvatore Di Fazio; Antonino Rollo; Viviana Tirella (Salehan Institute of Higher Education, 2022)
In recent years, global society has been subjected to great change due to unpredictable events such as pandemics, migrant flow, urban homeless, wars, and natural disasters. There has been an increased demand for fast and easily constructed buildings characterized by limited space and used for a limited time, modular and flexible self-assembly homes that are reusable without compromising comfort and environmental sustainability. A highly sustainable timber-cork modular system for lightweight temporary housing (LTH) is proposed in this paper. The structure of the proposed LTH was designed as a succession of modular timber portal frames composed of spruce boards hinged together. The concept of the prototype was a full modular shelter. It was possible to interchange every piece of the building, the structural elements, and the walls with each other. Due to the modularity of the elements of which the shelter was composed, this system could offer different solutions to the events above. The proposed LTH was analyzed in terms of its structural, thermal, and environmental performance. The structural system is very reminiscent of the platform frame, characterized by a light load-bearing frame consisting of solid timber uprights and crosspieces connected to the internal frame by means of a mechanical connection. The structural FEM analysis highlighted the structure’s capacity to withstand wind with a velocity of 72 m·s-1, corresponding to the F3 of the enhanced Fujita Scale (EF Scale) of tornado damage intensity. The thermal analysis highlighted a yearly energy use of 430.49 kWh to maintain a set-point temperature indoors of 20-26°C compared with a yearly energy use of 625.93 kWh for a common container house (CH) with the same dimensions under the same environmental conditions. Finally, a Life Cycle Analysis comparison between the proposed LTH and the CH was carried out by means of the One Click LCA software. Two different scenarios of service life were considered: one of 10 years and the other of 5 years. The results highlighted the higher sustainability of the proposed LTH than that of the CH for the required service life (Req SL) period. In particular, the calculated greenhouse gas emissions of the LTH (3.52103 kgCO2 eq) were less than 1/2 of the gas emissions of the CH (8.53103) for a Req SL of 10 years and about 1/3 for a Req SL of 5 years. Furthermore, the LTH showed a value of biogenic carbon storage (7.76E2 kgCO2) about 6 times bigger than the temporary house container (1.31E2 kgCO2). Doi: 10.28991/CEJ-2022-08-10-020 Full Text: PDF